Analysis of the Role of Training and Development in Improving Employee Performance at PT. Karya Muda Mandiri Bangkalan. - henik, yulis; Wispandono, Raden Mas Mochammad (Management Department of Economics and Business Of Trunojoyo Madura University, 2023)
PT. Karya Muda Mandiri Bangkalan is one of the companies engaged in providing heavy rental equipment, civil works, production of mineral water management, and steam washing which requires special skills. For that, the company has provided training for the employees, but it only runs for one year which causes frequent work accidents. The objectives of this study are to determine the role of training in improving employee performance at PT Karya Muda Mandiri Bangkalan and to determine the role of development in improving employee performance at PT Karya Muda Mandiri Bangkalan. This study is conducted by a qualitative method using purposive sampling method to select informants who are determined by several criteria. Technique of collecting data uses three ways by conducting in-depth interviews, observation and documentation. The results of this study are 1) After PT. Karya Muda Mandiri Bangkalan carries out training on employee performance, the company can improve the performance of its employees, can reduce the number of work accidents and can make the company better. 2) The role of development at PT. Karya Muda Mandiri Bangkalan is that the employee performance is getting better. From the training, employees gain new knowledge and new experiences so that their performance can be maximized and have a positive impact on the company and also for consumers. The conclusions of this study are 1) Performance training for employees of PT. Karya Muda Mandiri Bangkalan is getting better than before in heavy equipment operation, heavy equipment maintenance, mineral water management and mineral water management machine maintenance. 2) Development of employee performance at PT. Karya Muda Mandiri Bangkalan is getting better. When employees are included in the training, the development of employee knowledge, skills and behaviors that bring changes to the company can be seen. Employees can further increase the service users and the employee performance can also be maximized.